DETERMINAN INTERNAL STRUKTUR MODAL PADA PERUSAHAAN SEKTOR PROPERTY AND REAL ESTATE DI BURSA EFEK INDONESIA - Junaedi, I Komang; Baskara, I Gde Kajeng (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.10.TAHUN.2024DO - 10.24843/EEB.2024.v13.i10.p05, 2024)
The capital structure is important for a company because if it fails to determine its capital structure properly, the company will face financial difficulties and will affect the value of the company. The purpose of this study was to determine the effect of profitability, liquidity, asset structure, company growth, and company size on the capital structure of companies in the property and real estate sector on the Indonesia Stock Exchange for the 2020-2021 period. The samples used were 67 companies which were determined by purposive sampling method. This study uses quantitative data sourced from the Indonesia Stock Exchange which was collected using non-participant observation methods. The analysis technique uses multiple linear regression. The results showed that profitability and liquidity had a significant negative effect on capital structure, company growth had a significant positive effect on capital structure. However, the asset structure and company size have no significant effect on the capital structure of companies in the property and real estate sector on the Indonesia Stock Exchange for the 2020-2021 period. The implications of this study indicate that management can prioritize its own capital to fund investments and operations when the company is in a profitable and liquid position, while larger debt can be used when the company is growing rapidly.